Beyond Participation: What We Learned from Hunter about Collaboration with Pasifika Children and Families. (June 2014) - Cooper, Maria; Hedges, Helen
Increasing the participation rates of Pasifika children in early childhood settings is a policy target in Aotearoa — New Zealand. Yet, participation may not engender positive learning outcomes for children from diverse cultural backgrounds without attention to teacher knowledge and practice. The early childhood curriculum document, Te Whāriki, encourages teachers to collaborate with families. However, there is little research to guide teachers in mainstream centres to interpret Pasifika children's interests, particularly those that link with the understandings and everyday experiences of their families, communities or cultures. This article reports on a qualitative, interpretivist project. Findings related to a Pasifika child are presented. The child's overt interest in drumming led to deeper examination of his developing identities as a learner and member of his family and culture. The article argues that in order for diverse children and families to genuinely benefit from participation in early education teachers might usefully adopt more analytical, culturally responsive, and dialogic approaches and constructs to guide provision of a dynamic and responsive play-based curriculum. The use of theoretical frameworks such as funds of knowledge to assist families and centres to engage in and sustain reciprocal relationships and enhance collaboration to benefit children's growing learner and cultural identities is discussed.